2010
DOI: 10.1016/j.imbio.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

C1q induces a rapid up-regulation of P-selectin and modulates collagen- and collagen-related peptide-triggered activation in human platelets

Abstract: , C1q induces a rapid up-regulation of P-selectin and modulates collagen-and collagen-related peptidetriggered activation in human platelets, 2010, Immunobiology, (215), 12, 987-995 The aim of this study was to further characterize the effects of C1q on platelets, by quantifying the platelet surface expression of P-selectin (CD62P) and monitoring the formation of platelet-neutrophil aggregates. Using flow cytometry, we found that C1q dosedependently triggered a rapid but moderate and transient up-regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…In the same study we also observed that subsequent collagen or collagen-related peptide (GPVI specific)-induced activation of platelets was markedly inhibited [12]. Since the structure of C1q resembles that of collagen and C1q is described to bind to the collagen receptor ␣II␤I on mast cells [11] one may hypothesize that C1q exerts its inhibitory effects on collagen activation via binding to ␣II␤I, or GPVI.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In the same study we also observed that subsequent collagen or collagen-related peptide (GPVI specific)-induced activation of platelets was markedly inhibited [12]. Since the structure of C1q resembles that of collagen and C1q is described to bind to the collagen receptor ␣II␤I on mast cells [11] one may hypothesize that C1q exerts its inhibitory effects on collagen activation via binding to ␣II␤I, or GPVI.…”
Section: Discussionmentioning
confidence: 59%
“…P-selectin is often used as a marker of platelet activation and increased levels of both membrane-bound and soluble P-selectin have been reported during for example stroke, coronary artery disease and diabetes, reviewed in [31]. In a previous study, we speculated that the rapid and transient, but moderate up-regulation of P-selectin on the platelet surface caused by C1q was associated with shedding of the P-selectin molecule, leading to increased levels of soluble P-selectin in plasma [12]. This does not seem to be the case in a whole blood system as C1q per se did not increase the levels of soluble P-selectin.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Activation of platelets with potent agonists, including thrombin and arachidonic acid, promotes activation of the alternative complement pathway mediated via binding of C3b to P-selectin [131, 134]. C1q interaction with platelets has also been shown to induce expression of P-selectin on the platelet surface to potentially enhance complement activation via the alternative pathway [135]. C1q interaction with platelets also reduces collagen-mediated platelet activation via GPVI and platelet-neutrophil aggregate formation, a process dependent upon P-selectin interaction with PSGL-1 [77], suggesting a negative feedback on collagen-mediated platelet adhesion to potentially favour enhanced complement activation.…”
Section: The Complement System and Cardiovascular Diseasementioning
confidence: 99%